Modeling the temperature evolution of Svalbard permafrost during the 20th and 21st century. - Etzelmüller, Bernd; Schuler, Thomas Vikhamar; Isaksen, Ketil; Christiansen, Hanne Hvidtfeldt; Farbrot, Herman; Benestad, Rasmus (UNESCO/IOC, 2011)
Variations in ground thermal conditions in Svalbard were studied based on measurements and modelling. Ground temperature data from boreholes were used to calibrate a transient heat flow model describing depth and time variations in temperatures. The model was subsequently forced with historical surface air temperature records and possible future temperatures downscaled from multiple global climate models. We discuss ground temperature development since the early 20th century, and the thermal responses in relation to ground characteristics and snow cover. The modelled ground temperatures show a gradual increase between 1912 and 2010, by about 1.5 °C to 2 °C at 20 m depth. The active layer thickness (ALT) is modelled to have increased slightly, with the rate of increase depending on water content of the near-surface layers. The used scenario runs predict a significant increase in ground temperatures and an increase of ALT depending on soil characteristics.